VILNIAUS UNIVERSITETO BIBLIOTEKOS INKUNABULAI: RINKINIO RAIDA IR SUDĖTIS - RAČIUS, VIDAS (Knygotyra, 2011)
Vilniaus universiteto biblioteka Universiteto g. 3, LT-01122 Vilnius, Lietuva El. paštas: Petras.Racius@mb.vu.lt Šiuo metu Vilniaus universiteto bibliotekoje saugoma 315 spaudos pirmagimių knygų – inkunabulų. Fondo dydis įvairiuose šaltiniuose įvairuoja. Straipsnio siekis – išnagrinėti, kaip radosi ir kito Vilniaus universiteto bibliotekos inkunabulų fondas, kokie veiksniai darė įtaką tiems pokyčiams, kokia inkunabulų fondo apimtis, sudėtis, dabartinė būklė ir kokia inkunabulų reikšmė Lietuvos kultūrai. Reikšminai žodžiai: knyga, spauda, inkunabulas, paleotipas, biblioteka, katalogas, spaustuvininkas, raida. INCUNABULA IN VILNIUS UNIVERSITY LIBRARY: DEVELOPMENT AND STRUCTURE VIDAS RAČIUS Summary There are 315 incunabula in the Vilnius University Library now. The aim of the article was to examine how the fund of these incunabula was compiled and the amount of this fund was changing, what factors influenced changes of this fund, and what is the significance of these incunabula for Lithuanian culture. At the same time it was an attempt using incunabula to show at least passingly how Lithuania looked in European political, cultural and ideological context of that time, what events or processes influenced collection accession, who and by what ties related it to other countries. Lithuania was not a desert island on an European map, withdrawn from prevalent political cultural and ideological changes, neither it was a total barren, accepting no progress or novelties. It was inquired by what ways the incunabula emerged in our country, what was the demand and what impact they made, who and why acquired them, and what marks their activity had left so that we could judge by them about their circulation in Lithuanian cultural life and contemplate what still undiscovered treasures may be hidden in them waiting for researchers attention.